2021
DOI: 10.46827/ejpe.v6i11.3654
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning for Physical Education Students in Vietnam: Promises and Challenges

Abstract: The rise in mobile learning has seen an impressive increase as smartphones and tablets have increased in popularity in recent years. The cheap, easy access to these devices for students contributes to the need for use for educational and learning purposes. This trend is no exception for physical education. This study surveyed 125 physical education students in 4 badminton classes from 2018 to 2020 to evaluate their readiness for mobile learning in terms of hardware devices, technology skills, learning styles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This experimental study highlighted the need of employing effective tactics in online physical education sessions to motivate students. In contrast, Vu and Lien's [84] research of 125 physical education students in Vietnam revealed that the majority of them were prepared for mobile learning. However, students confront obstacles such as internet infrastructure and they required training for online learning skills.…”
Section: Mobile Applications-assisted Instruction and Physical Educat...mentioning
confidence: 88%
“…This experimental study highlighted the need of employing effective tactics in online physical education sessions to motivate students. In contrast, Vu and Lien's [84] research of 125 physical education students in Vietnam revealed that the majority of them were prepared for mobile learning. However, students confront obstacles such as internet infrastructure and they required training for online learning skills.…”
Section: Mobile Applications-assisted Instruction and Physical Educat...mentioning
confidence: 88%
“…Mobile learning (M-Learning) is the next advancement of online learning where the learning materials are received via mobile devices by the students. As Luong et al (2021) underscore, mobile learning is a type of learning that can be done anytime, anywhere in a handheld or palmtop device. The widespread availability and ownership of devices such as iPhones, iPads, and tablets have allowed users to access educational resources and activities which are related to their personal needs.…”
Section: Mobile Educationmentioning
confidence: 99%
“…In general, universities worldwide tend to integrate mobile applications and ICT into physical education. This trend continues to develop [ 19 ]. Nevertheless, the degree of integration may vary depending on the university and region, as well as on the availability of the necessary resources and technologies.…”
Section: Introductionmentioning
confidence: 99%